A New Bit Level Positional Encryption Algorithm (NBLPEA ver-1) - Nath, Asoke; Das, Sankar; Mazumder, Oishi; Saha, Adrija; Ghosh, Monimoy (International Journal of Computer Sciences and Engineering, 2020)
In the world of information we live in, cyber security is of paramount importance. Despite communicating through secure channels, there might be breaches that might be targeted by attackers to extract valuable data. Designing and betterment of these symmetric and asymmetric algorithms remain an open challenge to all. The Bitwise Positional Encryption Algorithm is a completely new idea in this field. This simple encryption technique provides strong protection against any kind of attack, be it brute force or statistical attacks. This multilevel encryption algorithm employs several bitlevel encryption procedures and matrix transposition operations. It takes into consideration positional parameters of bits, which is further shuffled randomly and hence is impossible for the intruder to decrypt without knowing the key as well as the exact method. The key here should be a shared parameter, for this is an instance of symmetric encryption. The algorithm works on bit-level so it is not possible to break easily. By this algorithm, one can encrypt any kind of file with extensions like .txt, .doc, .jpg, .png and the like. The present method can be used for encryption of any confidential messages like OTP (One Time Password), ATM transactions etc. It is not possible to get back the original plain text file if there is one change in bits in encrypted text. The testing is done on almost all types of files and it was found that the method is working satisfactorily.